Gasping in Response to Basic Resuscitation Efforts: Observation in a Swine Model of Cardiac Arrest - Mathias Zuercher; Gordon A. Ewy; Charles W. Otto; Ronald W. Hilwig; Bentley J. Bobrow; Lani Clark; Vatsal Chikani; Arthur B. Sanders; Robert A. Berg; Karl B. Kern (Critical Care Research and Practice)
Objective. To analyze the effect of basic resuscitation efforts on gasping and of gasping on survival. Methods. This is secondary analysis of a previously reported study comparing continuous chest compressions (CCC CPR) versus chest compressions plus ventilation (30:2 CPR) on survival. 64 swine were randomized to 1 of these 2 basic CPR approaches after either short (3 or 4 minutes) or long (5 or 6 minutes) durations of untreated VF. At 12 minutes of VF, all received the same Guidelines 2005 Advanced Cardiac Life Support. Neurologically status was evaluated at 24 hours. A score of 1 is normal, 2 is abnormal, such as not eating or drinking normally, unsteady gait, or slight resistance to restraint, 3 severely abnormal, where the animal is recumbent and unable to stand, 4 is comatose, and 5 is dead. For this analysis a neurological outcome score of 1 or 2 was classified as “good”, and a score of 3, 4, or 5 was classified as “poor.” Results. Gasping was more likely to continue or if absent, to resume in the animals with short durations of untreated VF before basic resuscitation efforts. With long durations of untreated VF, the frequency of gasping and survival was better in swine receiving CCC CPR. In the absence of frequent gasping, intact survival was rare in the long duration of untreated VF group. Conclusions. Gasping is an important phenomenon during basic resuscitation efforts for VF arrest and in this model was more frequent with CCC-CPR.